2023
DOI: 10.1038/s41598-023-43430-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of high-performance supercapacitor electrode with nanocomposite of CuO/NCNO flower-like

Esmail Sohouli,
Hakimeh Teymourinia,
Ali Ramazani
et al.

Abstract: Due to the importance of energy storage systems based on supercapacitors, various studies have been conducted. In this research CuO, NCNO and the flower like CuO/NCNO have been studied as a novel materials in this field. The resulte showed that the synthesized CuO nanostructutes have flower like morphology which studied by FE-SEM analisis. Further, the XRD pattern confirmed the crystalline properties of the CuO/NCNO nanocomposite, and the Raman verified the functional groups and vibrations of the components of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…25 Therefore, the combination of CuO@Cu 4 O 3 /rGO can form an electron-conducting network with a short charge diffusion path that enhances the charge transfer process and improves the supercapitance performance. 26,27 Much previous literature has reported the supercapacitance performance of the CuO nanomaterial electrodes. For example, Shivaji et al reported a specic capacitance of 57.44 F g −1 for CuO lm in 1.0 M KOH electrolyte deposited by the electrodeposition protocol.…”
Section: Introductionmentioning
confidence: 99%
“…25 Therefore, the combination of CuO@Cu 4 O 3 /rGO can form an electron-conducting network with a short charge diffusion path that enhances the charge transfer process and improves the supercapitance performance. 26,27 Much previous literature has reported the supercapacitance performance of the CuO nanomaterial electrodes. For example, Shivaji et al reported a specic capacitance of 57.44 F g −1 for CuO lm in 1.0 M KOH electrolyte deposited by the electrodeposition protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, CuO is converted to its metallic form during charging and then returned to its original state by discharge. These reversible redox reactions facilitate the effective storage and discharge of electrical energy, hence contributing to the elevated capacitance of supercapacitors 15 17 . The transition metal hydroxide or oxide materials, such as Co (OH) 2 , Ni (OH) 2 , Co 2 O 3 , and NiO, are commonly employed in merged with nanostructure to enhance the mechanical characteristics and surface area of the electrode 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%